Trend Analysis of Shrimp (Penaeus sp.) Production at Jambean Fishing Port, Pekalongan Regency, Central Java - Siti Maharani; Audia Ramadani; Fadilah Aulia; Muhammad Rafi; Sudirman Adibrata; Martin Yermias Luhulima (Yayasan Serumpun Karang Konservasi, 2025)
Shrimp (Penaeus sp.) is one of the most economically important fishery commodities in Indonesia, contributing significantly to the capture fisheries sector and coastal community livelihoods. Monitoring shrimp production trends is essential to support sustainable fisheries management, particularly in the Indonesia Fisheries Management Area (IFMA) 712. This study aimed to analyze shrimp production trends, production value, and estimate the utilization potential of shrimp resources landed at Jambean Fishing Port, Pekalongan, during the 2020–2024 period. A quantitative descriptive approach was employed using secondary data obtained from the Statistical Data Portal of the Ministry of Marine Affairs and Fisheries of the Republic of Indonesia. The data consisted of annual shrimp production volume and production value, which were analyzed using descriptive statistics, tables, graphical trend analysis, and average production calculations. The results showed that shrimp production fluctuated throughout the study period, with the lowest production recorded in 2022 (42.19 tons) and the highest production in 2024 (74.37 tons). Similarly, shrimp production value exhibited a fluctuating trend, reaching its highest value of IDR 3,346,695 thousand in 2024. The average shrimp production during the five-year observation period was 55.44 tons. These findings indicate that shrimp resources in the study area continue to provide considerable economic potential. However, increasing fishing activities should be accompanied by sustainable fisheries management through continuous production monitoring and appropriate resource utilization strategies to maintain shrimp stock sustainability in IFMA 712.